The role of procalcitonin as a biomarker for acute pulmonary exacerbation in subjects with cystic fibrosis and non-cystic fibrosis bronchiectasis - KOCAKAYA, DERYA; ARIKAN, HÜSEYİN; ERYÜKSEL, SEMİHA EMEL; CEYHAN, BERRİN (My University, 2022)
Objective: Patients with cystic fibrosis (CF) and non-CF bronchiectasis are prone to exacerbations of pulmonary infections. C-reactive protein (CRP) and procalcitonin (PCT) are inflammatory markers. The aim of this study is to evaluate the role of CRP and PCT on exacerbations of CF and non-CF bronchiectasis. Patients and Methods: The medical records of 18 CF (52 hospitalizations) and 20 non-CF bronchiectasis patients (51 hospitalizations) were reviewed retrospectively. CRP, PCT levels and, white blood cell (WBC) counts on admission and follow-up were evaluated. Results: C-reactive protein levels correlated with PCT levels on admission in all patients. Baseline PCT levels were markedly higher (>0.5µg/L) in 12% of CF and 10% of non-CF bronchiectasis patients, however, baseline CRP values were markedly higher (>5mg/L) in 96% of CF and non-CF bronchiectasis patients (p=0.760 and p=0.100, respectively). Baseline CRP and PCT levels were positively correlated with hospitalization length (r=0.501, p=0.001 and r=0.289, p=0.04, respectively) in CF patients, but not in non-CF bronchiectasis. Conclusion: Our study shows the potential utility of these biomarkers to determine the severity of the exacerbation particularly predicting hospitalization length in CF patients. Both biomarkers could be able to guide antibiotic treatment of infective exacerbations in CF and non-CF bronchiectasis patients.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Cystic fibrosis; Bronchiectasis; Exacerbation; Infection; Procalcitonin; C-reactive protein; C-REACTIVE PROTEIN; SERUM PROCALCITONIN; ADULT PATIENTS; PATHOPHYSIOLOGY; INFECTIONS; GUIDANCE; THERAPY; MARKERS; Cystic fibrosis; Bronchiectasis; Exacerbation; Infection; Procalcitonin; C-reactive protein